Effects of health education and counselling intervention on stress among women diagnosed with breast cancer in Yemen - Abdo, Ahmed Ali Ahmed (2019)
The breast cancer is the most common type of cancer, accounting for 32.3% of all reported cancers in Yemen. It is the most frequently diagnosed life-threatening illnesses in women; it is greatly affect all spheres of women's life. Being diagnosed and living with cancer is a very stressful experience and having a serious impact on many aspects of women’ daily life. Which make them prone to psychological and emotional disturbances, low quality of life, and leaves dramatic and adverse effects on their life. However, no cancer center in Yemen provide psychosocial support to the cancer patients. Moreover, there is high illiteracy particularly among women, and limited knowledge and understanding of breast cancer and its psychosocial implications. The aim of this study is to develop, implement and evaluate the effect of the educational and counseling intervention on the stress, mental adjustment and quality of life in Yemeni breast cancer. The study design is a quasi-experimental repeated measure with a comparison group. The study had been conducted in Yemen, in which 56 participants were placed in each of the two groups, a control and intervention group. The participants in intervention group had been selected randomly from the National Oncology Center in Sana'a, while the participants of control group were selected from the National Oncology Centers in Aden and Hadhramaut by using purposive sampling method. To evaluate the effects of the intervention, data were collected at baseline, 2 months and six months after intervention in both intervention and control groups. The outcomes were measured by using the PSS-10 item scale, Mini-MAC scale, QLQ-C30 questionnaires and QLQBR23 questionnaires. The analysis had been conducted on 102 out of 112 participants (91%); 50 (89%) control group, and 52 (93%) intervention group. The results showed that the education and counseling intervention reduced the perceived stress score (p value < 0.05), improved the mental adjustment score (p value < 0.05) of all domains except for the fatalism (p = 0. 54). As well as, the intervention has affected on the QoL in three domains; global health status, emotional functioning and future perspective (p value < 0.05), but the intervention did not show any effect on three QoL domains; the physical functioning, role functioning and body image domains were statistically nonsignificant. The findings showed that the intervention reduced the level of stress, improved the mental adjustment with breast cancer and the most of the quality of life domains, with less non-significant effect on the body image, role functioning and physical functioning domains of quality of life, in particular, in the first three months of breast cancer diagnosis.